Предмет: Математика,
автор: saxinerah
Разложите на множители
Приложения:
Ответы
Автор ответа:
1
Ответ:
Пошаговое объяснение:
ab(a-b)-ac(a-c)+bc(b-c)=
ab(a-b)-a²c+ac²+b²c-bc²=
ab(a-b)-c(a²-b²)+c²(a-b)=
ab(a-b)-c(a+b)(a-b)+c²(a-b)=
(a-b)(ab-c(a+b)+c²)=
(a-b)(ab-ac-bc+c²)=
(a-b)(a(b-c)-c(b-c))=
(a-b)(a-c)(b-c)
Похожие вопросы
Предмет: Алгебра,
автор: aminkamasharipova200
Предмет: Информатика,
автор: Stasyaytt
Предмет: Українська мова,
автор: mariazagumennaya
Предмет: История,
автор: катя606
Предмет: История,
автор: НУБЯРАКОТЯРА1209